Analisis Efektivitas Sistem Informasi Manajemen Rumah Sakit (SIMRS) Di Rsud Regional Mamuju - A.Munawarah Rasyidi Ms; Salsa Dila Putri; Hari Yeni (CV. SINAR HOWUHOWU, 2026)
The use of a Hospital Management Information System (SIMRS) is a crucial element in supporting improvements in the quality of healthcare services, operational efficiency, and accuracy in managerial decisions. Mamuju Regional Hospital, which serves as a referral hospital in West Sulawesi Province, has implemented SIMRS to assist medical services and hospital management activities. This study was conducted to assess the effectiveness of SIMRS use at Mamuju Regional Hospital, West Sulawesi. The method applied was descriptive with a qualitative approach. Data collection was carried out through interviews, field observations, and documentation studies involving SIMRS users, including health workers, administrative staff, and management. The data obtained were analyzed using data reduction, data compilation, and conclusion drawing steps. The results of the study indicate that the implementation of SIMRS has contributed to accelerating the service process, increasing the efficiency of patient data management, and providing more integrated and accurate information. However, the implementation of SIMRS has not been fully optimized due to obstacles such as a lack of human resource competence in information technology, system network disruptions, and variations in user understanding of the application. From the results of this study, it can be concluded that SIMRS at Mamuju Regional Hospital is quite effective, but still requires development through increasing user capacity, improving technology infrastructure, and continuous system evaluation to support better hospital services.